Design method and system of full-perovskite laminated solar cell and solar cell
By using physical simulation models and metaheuristic optimization algorithms to optimize structural parameters in all-perovskite stacked solar cells, the problem of large light reflection loss is solved, efficient photoelectric conversion and specific position anti-reflection effect is achieved, and the performance and cost-effectiveness of the battery are improved.
Patent Information
- Application Number
- CN202510288490.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
AI Technical Summary
The light reflection loss of all-perovskite stacked solar cells is large, which seriously limits the increase in photocurrent. The existing anti-reflection scheme is complex and costly, making it difficult to directly apply to all-perovskite stacked batteries.
Based on the physical simulation model and metaheuristic optimization algorithm, the fitness function is calculated and iteratively optimized to obtain the best physical parameters. By adjusting the thickness of a specific layer or introducing alternative materials, the photoelectric conversion efficiency is improved, and specific position anti-reflection effect is achieved in asymmetric multi-film systems.
The photocurrent of all-perovskite stacked solar cells has been significantly improved, the experimental cost has been reduced, and the efficient anti-reflection effect under the existing preparation process has been achieved, breaking the traditional limitation on the thickness of the interconnect layer.
Smart Images

Figure CN119808602A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a design method and system for an all-perovskite stacked solar cell and a solar cell. Background Art
[0002] Compared with silicon, perovskite materials have the advantages of continuously adjustable band gap, production through low-cost manufacturing technologies such as solution processing or printing methods, and the ability to prepare flexible devices. The stacking technology vertically stacks solar cell materials with different band gaps to more efficiently capture and convert different parts of the solar spectrum. This design allows the stacked cells to absorb sunlight over a wider band and effectively reduce the thermal loss of high-energy photons, thereby providing higher photoelectric conversion efficiency than traditional single-junction solar cells. Therefore, all-perovskite stacked solar cells have huge application potential and market competitiveness in the future photovoltaic field, and are expected to surpass traditional silicon-based solar cells in terms of cost and efficiency.
[0003] Traditional solar cells often use a multi-layer planar thin film stacking structure, which easily causes interference effects of light inside the cell, resulting in large light reflection energy loss, which seriously limits the conversion efficiency. Due to its material properties, silicon solar cells can prepare pyramid-shaped micro-nano structures inside the cell by chemical etching and other means. This micro-nano structure can effectively reduce light reflection loss and greatly improve the photocurrent, thereby making the conversion efficiency of solar cells leap. However, due to the significant differences between the materials and production processes used in perovskite solar cells and traditional silicon solar cells, the pyramid-shaped micro-nano structure used in traditional silicon solar cells cannot be realized in all-perovskite stacked cells. The current highest record of the efficiency of all-perovskite stacked solar cells is 29.1%. However, this is still a very large gap from the theoretical limit, and the main factor affecting the efficiency of stacked devices is the large light reflection loss inside the stacked cell, which seriously limits the improvement of photocurrent. Therefore, finding a method to reduce reflected light loss suitable for all-perovskite stacked solar cells has become a hot spot in current technological development.
[0004] In addition, 1. Most of the existing anti-reflection and enhanced absorption structures in solar cells are various micro-nano structures such as pyramidal and sinusoidal shapes. The preparation process is complex and the cost is high. In addition, the micro-nano structure easily reduces the opening voltage and filling factor of the battery, which reduces the photoelectric conversion efficiency. In addition, the micro-nano structure is mostly used in silicon / perovskite tandem cells, and it is currently difficult to directly apply it to all-perovskite tandem cells because of the relatively soft lattice of perovskite. Therefore, there is a lack of practical and effective anti-reflection solutions in the field of all-perovskite tandem cells.
[0005] 2. The existing all-perovskite stacked battery structure requires a large number of experimental preparations and complex characterization techniques to be designed and optimized. The design process consumes a lot of materials, is time-consuming, has many limiting factors, and it is difficult to find the optimal structural design solution.
[0006] 3. The existing optimization results obtained by combining algorithms with simulation models lack detailed theoretical analysis and support, and the structural parameters given by the algorithm are difficult to directly apply to experimental preparation. Therefore, the beneficial effects of the structure optimized by the current algorithm need to be verified theoretically or experimentally. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention is proposed.
[0008] To solve the above technical problems, in the first aspect, the present invention provides the following technical solutions: a design method for an all-perovskite tandem solar cell, comprising: establishing a physical simulation model based on the actual parameters of the all-perovskite tandem cell to be optimized; constructing a fitness function according to the performance indicators of the all-perovskite tandem cell; connecting a meta-heuristic optimization algorithm to the physical simulation model to calculate the fitness function and continuously iterate to obtain the optimal physical parameters of the all-perovskite tandem cell under the optimal fitness conditions; analyzing the optical interference effect of the all-perovskite tandem cell based on the optimal physical parameters, and improving its photoelectric conversion efficiency by adjusting the thickness of a specific layer or introducing alternative materials.
[0009] As a preferred scheme of the design method of the all-perovskite tandem solar cell described in the present invention, wherein: the structure of the all-perovskite tandem solar cell is a transparent substrate, a transparent electrode layer, a first hole transport layer, a wide bandgap perovskite layer, a first electron transport layer, a carrier recombination layer, a second hole transport layer, a narrow bandgap perovskite layer, a second electron transport layer and a metal electrode in sequence along the incident light; wherein the first electron transport layer, the carrier recombination layer and the second hole transport layer form an interconnected layer.
[0010] As a preferred solution of the design method of the all-perovskite tandem solar cell of the present invention, the fitness function is expressed as: F=J 宽带隙 +J 窄带隙 Among them, F is the fitness function value, J 窄带隙 is the narrow bandgap subcell current, J 宽带隙 is the wide bandgap sub-cell current.
[0011] As a preferred solution of the design method of the all-perovskite tandem solar cell described in the present invention, the meta-heuristic optimization algorithm includes but is not limited to a multiverse optimization algorithm, a zebra optimization algorithm and a genetic algorithm.
[0012] As a preferred solution of the design method of the all-perovskite tandem solar cell of the present invention, wherein: the peak position of the coherent reflection peak generated by the all-perovskite tandem solar cell in the 300~700nm band is adjusted by adjusting the thickness of the transparent electrode layer.
[0013] As a preferred solution of the design method of the all-perovskite tandem solar cell of the present invention, wherein: by adjusting the thickness of the interconnect layer, the coherent reflection phenomenon of the all-perovskite tandem solar cell in the 700~1000nm band is weakened.
[0014] As a preferred solution of the design method of the all-perovskite tandem solar cell of the present invention, when the thickness value of the optimized interconnection layer exceeds the experimentally preparable range, the thickness of the interconnection layer is reduced and the thickness is compensated by other alternative materials.
[0015] As a preferred solution of the design method of the all-perovskite tandem solar cell of the present invention, when the material of the interconnection layer is SnO 2 When the alternative material is indium tin oxide.
[0016] In a second aspect, the present invention further provides a design system for an all-perovskite tandem solar cell, which is applicable to the above-mentioned design method for an all-perovskite tandem solar cell.
[0017] In a third aspect, the present invention further provides an all-perovskite tandem solar cell, which is manufactured by the above-mentioned design method of the all-perovskite tandem solar cell.
[0018] The beneficial effects of the present invention are as follows: 1. The present invention is designed based on a full-plane structure of mechanical stacking, thereby avoiding the opening pressure loss and fill factor reduction caused by the micro-nano structure; 2. All-perovskite stacked solar cells are asymmetric multi-thin film systems, and the common anti-reflection film system uses a symmetric thin film system, which cannot be directly applied. Secondly, due to the complex internal light propagation mechanism of the asymmetric multi-thin film system, usually only 2 to 3 layers of film are used for design, and it is very difficult to design a thin film system with more than ten layers of cells. Thirdly, the multi-layer film system usually plays an anti-reflection role as a whole, and it is rare to perform functional design on specific positions within the thin film system. Moreover, after the specific position is modified to achieve a specific function, the entire thin film system is still required to retain the original effect, which is very difficult. The present invention achieves a significant specific position anti-reflection effect in an asymmetric multi-thin film system using only the existing common preparation process, greatly improving the photocurrent of the battery.
[0019] 3. The present invention combines advanced intelligent algorithms with physical simulation models to quickly perform fully automated optimal structural design, without the need for large-scale experimental exploration of optimized structures, effectively reducing experimental costs. In addition, the advanced intelligent algorithms and physical simulation models of the present invention are universal and can be applied to solar cells of different materials and structures.
[0020] 4. It is generally believed in the industry that the thickness of the interconnection layer should be reduced as much as possible to prevent the parasitic absorption of the functional layer from affecting the absorption of the perovskite. The present invention breaks this inherent concept and achieves a significant specific position anti-reflection effect in the asymmetric multi-thin film system by thickening some materials in the interconnection layer, greatly improving the photocurrent of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 A logical flow chart of the design method for all-perovskite tandem solar cells.
[0023] Figure 2 The structure of an actual all-perovskite tandem solar cell for reference.
[0024] Figure 3 The reflectivity, absorptivity curve and photocurrent calculated by the simulation model before optimization.
[0025] Figure 4 Comparison chart of reflectivity, absorption rate curves and photocurrent size calculated by the simulation model after and before algorithm optimization.
[0026] Figure 5 Analysis diagram of the numerical relationship and phase relationship between the reflectivity before optimization and the interface reflected light.
[0027] Figure 6 Comparison chart of reflected light intensity before and after optimization of the interconnect layer.
[0028] Figure 7 This is a comparison chart of the reflectivity, absorption rate curve and photocurrent size before and after ITO replacement.
[0029] Figure 8 This is the structure of the actual all-perovskite tandem solar cell used as a reference in Example 2.
[0030] Fig. 9The reflectivity, absorptivity curve and photocurrent size calculated by the simulation model before optimization in Example 2.
[0031] Fig.10 The reflectivity, absorptivity curves and photocurrent size comparison diagram calculated by the simulation model after and before optimization in Example 2.
[0032] In the figure: 1. transparent substrate; 2. transparent electrode layer; 3. first hole transport layer; 4. wide band gap perovskite layer; 5. first electron transport layer; 6. carrier recombination layer; 7. second hole transport layer; 8. narrow band gap perovskite layer; 9. second electron transport layer; 10. metal electrode; H. interconnect layer. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.
[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0035] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it an embodiment that is mutually exclusive with other embodiments, either individually or selectively.
[0036] Reference Figure 1 to Figure 7 , which is the first embodiment of the present invention, provides a design method for an all-perovskite tandem solar cell, the method comprising: Step 1: Establish a physical simulation model based on the actual parameters of the all-perovskite tandem battery to be optimized.
[0037] Specifically, a physical simulation model is established based on finite element simulation software. The structure of the actual all-perovskite tandem solar cell is shown in the figure. Figure 2 As shown, from the direction of incident light, they are: transparent substrate 1, transparent electrode layer 2, first hole transport layer 3, wide bandgap perovskite layer 4, first electron transport layer 5, carrier recombination layer 6, second hole transport layer 7, narrow bandgap perovskite layer 8, second electron transport layer 9 and metal electrode 10.
[0038] The transparent substrate 1 is a photovoltaic glass substrate; the transparent electrode layer 2 is an ITO transparent electrode with a thickness of 150nm; the material of the first hole transport layer 3 is NiOx , thickness 20nm; the thickness of the wide bandgap perovskite layer 4 is 420nm; the first electron transport layer 5 is composed of two layers of materials, namely C 60 and SnO 2 , thicknesses of 20nm and 30nm respectively; the material of the carrier recombination layer 6 is Au, with a thickness of 0.4nm; the material of the second hole transport layer 7 is PEODT:PSS, with a thickness of 40nm; the narrow bandgap perovskite layer 8, with a thickness of 1200nm; the second electron transport layer 9 is composed of two layers of materials, namely C 60 and BCP, with thicknesses of 20nm and 7nm respectively; the metal electrode 10 is made of Cu, with a thickness of 20nm.
[0039] Step 2: Construct a fitness function based on the performance indicators of the all-perovskite tandem battery.
[0040] Specifically, the expression of the fitness function is: F=J 宽带隙 +J 窄带隙 Among them, F is the fitness function value, J 窄带隙 is the narrow bandgap subcell current, J 宽带隙 is the wide bandgap sub-cell current.
[0041] Step three: Connect the meta-heuristic optimization algorithm to the physical simulation model to calculate the fitness function and continuously iterate to obtain the optimal physical parameters of the all-perovskite tandem battery under the optimal fitness conditions.
[0042] Specifically, the finite element method is used to solve the light field distribution inside the device, and the corresponding reflectivity, absorptivity, transmittance and photocurrent are calculated. The results are as follows: Figure 3 shown.
[0043] In the model, except for the transparent substrate 1, the BCP layer in the second electron transport layer 9 and the metal electrode 10, the thickness of each layer is a combination of parameters controlled by the algorithm. The thickness of each layer varies as follows: transparent electrode layer 2, thickness 40~250nm; first hole transport layer 3, thickness 10~80nm; wide bandgap perovskite layer 4, thickness 300~600nm; C in the first electron transport layer 5, thickness 200~250nm; 60 layer, thickness 10~120nm, SnO 2 layer, with a thickness of 10-150nm; carrier recombination layer 6, with a thickness of 0.1-2nm; second hole transport layer 7, with a thickness of 20-100nm; narrow bandgap perovskite layer 8, with a thickness of 600-1600nm; C in the second electron transport layer 9 60 Layer, thickness 10~120nm.
[0044] The maximum number of iterations is set to 1000. The algorithm uses MATLAB to construct the zebra optimization algorithm and substitutes the randomly initialized parameter combination into the simulation model for calculation, and obtains the corresponding fitness function value. The parameter combination with higher fitness value is retained, and the parameter combination with lower fitness value is eliminated. The parameters are modified based on the parameter combination with high fitness value to generate a new parameter combination and substitute it into the model calculation again. Iterate continuously until the maximum number of iterations or the fitness value target is reached, and finally the optimized parameter combination is given. The reflectivity, transmittance, absorptivity and photocurrent obtained by calculating the parameter combination optimized by the zebra optimization algorithm are shown in Figure 2. Figure 4 The optimization parameter combinations given by the algorithm are shown in Table 1.
[0045] Table 1 Reflectivity, transmittance, absorptivity and photocurrent calculated by the parameter combination optimized by the zebra optimization algorithm , Step 4: Analyze the optical interference effect of the all-perovskite tandem cell based on the optimal physical parameters, and improve its photoelectric conversion efficiency by adjusting the thickness of a specific layer or introducing alternative materials.
[0046] Specifically, although the optimization results given by the algorithm are very good, the values of some parameters do not meet the conditions of experimental preparation. Therefore, it is necessary to conduct a detailed physical principle analysis of the optimization results given by the algorithm, and by analyzing the implementation principle of the optimal solution, redesign the structure of the battery so that it can maintain superior performance while meeting the conditions of experimental preparation.
[0047] By using the transmission matrix method to analyze, it is found that the physical principle of the reflected light interference effect of the device is as follows: like Figure 5 As shown, for the 300~700nm band, the reflected light is mainly caused by the coherent enhancement of the Fresnel reflection at the interface of the transparent substrate 1-transparent electrode layer 2 and the Fresnel reflection at the interface of the first hole transport layer 3-wide band gap perovskite layer 4; for the 700~1000nm band, for the convenience of theoretical explanation, the first electron transport layer 5, the carrier recombination layer 6 and the second hole transport layer 7 are collectively referred to as the interconnection layer, and the overall reflectivity is calculated by the transmission matrix. It is not difficult to find that the reflected light in this band is mainly caused by the coherent enhancement of the Fresnel reflection at the interface of the first hole transport layer 3-wide band gap perovskite layer 4 and the overall reflection of the interconnection layer.
[0048] By comparing the parameter combinations and reflectivity curves before and after optimization, it is not difficult to find that adjusting the thickness of the transparent electrode layer 2 can adjust the peak position of the coherent reflection peak generated in the 300-700nm band. By reducing the thickness of the transparent electrode layer 2, the characteristic peak of the reflection peak can be adjusted to below 350nm, thereby avoiding its influence on the spectral absorption of the battery. Thickening the interconnect layer H can effectively solve the coherent reflection enhancement in the 700~1000nm band. The principle is as follows Figure 6 As shown, the thickness of the interconnection layer H is thinner before optimization, and the reflected light intensity of the interconnection layer is higher before optimization. The thickness of the interconnection layer H is thicker after optimization, and the reflected light intensity of the interconnection layer is significantly reduced after optimization. Therefore, the coherence phenomenon between the interconnection layer H and the reflected light at the interface of the first hole transport layer 3-wide bandgap perovskite layer 4 is not obvious, thereby effectively reducing the reflected light loss and improving the overall absorption rate of the battery.
[0049] However, the 150nm thick SnO 2 Obviously, it has far exceeded the reasonable range that can be prepared experimentally, so it is necessary to modify the battery structure and design the material and structure into a reasonable structure that can be prepared experimentally while retaining similar properties such as reflectivity, transmittance, absorptivity and photocurrent intensity.
[0050] It is not difficult to imagine that by using SnO 2 There are similar refractive index, conductive, intrinsic materials to partially replace SnO 2 layer, splitting the overly thick first electron transport layer 5 into SnO 2 Layers and thicker layers of alternative materials can achieve similar anti-reflection effects.
[0051] Through the trial and study of various materials, and considering the feasibility of experimental preparation and material cost, ITO was selected as an alternative material. At the same time, ITO can replace the carrier recombination layer (Au) as the carrier recombination center, and further design the material thickness according to the conclusion of theoretical analysis. The design structure parameters are shown in Table 2.
[0052] Table 2 Thickness of various materials designed based on the conclusions of theoretical analysis , The reflectivity, absorptivity and photocurrent of the battery before and after ITO material replacement are as follows Figure 7 As shown in the figure, due to the high parasitic absorption of ITO, the overall photocurrent will be slightly reduced compared to before replacement, which is a better trade-off for experimental feasibility.
[0053] As an optional embodiment, refer to Figure 8~Figure 10 The present invention also provides a design method for all-perovskite tandem solar cells using other algorithms, specifically: based on the transfer matrix method, a physical simulation model is established using MATLAB. The structure of the actual all-perovskite tandem solar cell is shown in FIG. Figure 8 As shown, the first hole transport layer 3 is a SAM self-assembled molecular layer; the material of the carrier recombination layer 6 is IZO; the rest of the structure and thickness are the same as Figure 1Same as in.
[0054] The electric field intensity distribution inside the battery is solved by the transfer matrix method, and the corresponding reflectivity, absorptivity, transmittance and photocurrent are calculated based on the complex refractive index of the material. The results are as follows: Fig. 9 shown.
[0055] In the model, except for the transparent substrate 1, the first hole transport layer 3, the BCP layer in the second electron transport layer 9, and the metal electrode 10, the thickness of each layer is a combination of parameters controlled by the algorithm. The thickness of each layer varies from 40 to 250 nm for the transparent electrode layer 2, 300 to 600 nm for the wide bandgap perovskite layer 4, and 500 to 600 nm for the C in the first electron transport layer 5. 60 Layer thickness is 10~120nm, SnO 2 The thickness of the layer is 10~60nm; the carrier recombination layer 6 has a thickness of 40~200nm; the second hole transport layer 7 has a thickness of 20~100nm; the narrow bandgap perovskite layer 8 has a thickness of 600~1600nm; the C in the second electron transport layer 9 60 Layer thickness 10~120nm.
[0056] The fitness function is set as F=J 宽带隙 +J 窄带隙 Among them, F is the fitness function value, J 窄带隙 is the narrow bandgap subcell current, J 宽带隙 is the wide bandgap sub-battery current. The maximum number of iterations is set to 1000 times. The algorithm uses MATLAB to build a multi-task parallel computing algorithm, and uses the zebra optimization algorithm, genetic algorithm, and multiverse optimization algorithm to synchronously and independently call the simulation model. The initial parameter combinations are randomly generated and substituted into the simulation model for calculation and obtain the corresponding fitness function value. The parameter combinations with higher fitness values are retained, and the parameter combinations with lower fitness values are eliminated. The parameters are modified based on the parameter combinations with high fitness values to generate new parameter combinations and then substituted into the model for calculation again. Iterate continuously until the maximum number of iterations or the fitness value target is reached, and finally the optimized parameter combinations are independently given.
[0057] This multi-task parallel computing algorithm can use three different advanced optimization algorithms to independently perform optimization iterative calculations at the same time, and give the corresponding optimized results independently. This method can greatly ensure that the optimization process jumps out of the local optimal solution and finds the global optimal performance parameter combination of the simulation model as much as possible.
[0058] The optimization parameter combinations given by the algorithm are shown in Table 3.
[0059] Table 3 The optimal performance parameter combination of each algorithm after optimization , It can be seen that the optimized parameter combinations given by the three algorithms are all within a similar range. A physical principle analysis similar to that in the previous embodiment is performed on the device of this structure, and a reasonable parameter combination is given after combining the experimental practice as shown in Table 4.
[0060] Table 4 Reasonable parameter combinations given based on experimental practice , The optimized parameter combination is substituted into the model to calculate the reflectivity, absorptivity and photocurrent. Fig.10 As shown. Obviously, this parameter combination not only obtains excellent photocurrent intensity but also meets the requirements of experimental preparation.
[0061] In summary, the beneficial effects of the present invention are: 1. The present invention is designed based on a full-plane structure of mechanical stacking, which avoids the experimental preparation difficulties, opening pressure loss and fill factor reduction caused by micro-nano structures; 2. All-perovskite stacked solar cells are asymmetric multi-thin film systems, and the common anti-reflection film system uses a symmetric thin film system, which cannot be directly applied. Secondly, due to the complex internal light propagation mechanism of the asymmetric multi-thin film system, usually only 2 to 3 layers of film are used for design, and it is very difficult to design a thin film system with more than ten layers of cells. Thirdly, the multi-layer film system usually plays an anti-reflection role as a whole, and it is rare to perform functional design on specific positions within the thin film system. Moreover, after the specific position is modified to achieve a specific function, the entire thin film system is still required to retain the original effect, which is very difficult. The present invention achieves a significant specific position anti-reflection effect in an asymmetric multi-thin film system using only the existing common preparation process, greatly improving the photocurrent of the battery.
[0062] 3. The present invention combines advanced intelligent algorithms with physical simulation models to quickly perform fully automated optimal structural design, without the need for large-scale experimental exploration of optimized structures, effectively reducing experimental costs. In addition, the advanced intelligent algorithms and physical simulation models of the present invention are universal and can be applied to solar cells of different materials and structures.
[0063] 4. It is generally believed in the industry that the thickness of the interconnection layer should be reduced as much as possible to prevent the parasitic absorption of the functional layer from affecting the absorption of the perovskite. The present invention breaks this inherent concept and achieves a significant specific position anti-reflection effect in the asymmetric multi-thin film system by thickening some materials in the interconnection layer, greatly improving the photocurrent of the battery.
[0064] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A design method for an all-perovskite tandem solar cell, characterized in that: include, Establish a physical simulation model based on the actual parameters of the all-perovskite tandem battery to be optimized; Constructing a fitness function according to the performance indicators of the all-perovskite tandem battery; Connecting a meta-heuristic optimization algorithm to the physical simulation model to calculate the fitness function and continuously iterate to obtain the optimal physical parameters of the all-perovskite tandem battery under the optimal fitness condition; The optical interference effect of the all-perovskite tandem cell is analyzed based on the optimal physical parameters, and its photoelectric conversion efficiency is improved by adjusting the thickness of a specific layer or introducing alternative materials.
2. The design method of the all-perovskite tandem solar cell according to claim 1, characterized in that: The structure of the all-perovskite stacked cell is, in order along the incident light, a transparent substrate (1), a transparent electrode layer (2), a first hole transport layer (3), a wide bandgap perovskite layer (4), a first electron transport layer (5), a carrier recombination layer (6), a second hole transport layer (7), a narrow bandgap perovskite layer (8), a second electron transport layer (9) and a metal electrode (10); wherein the first electron transport layer (5), the carrier recombination layer (6) and the second hole transport layer (7) form an interconnection layer (H).
3. The design method of the all-perovskite tandem solar cell according to claim 2, characterized in that: The expression of the fitness function is: F=J 宽带隙 +J 窄带隙 Among them, F is the fitness function value, J 窄带隙 is the narrow bandgap subcell current, J 宽带隙 is the wide bandgap sub-cell current.
4. The design method of the all-perovskite tandem solar cell according to claim 3, characterized in that: The meta-heuristic optimization algorithm includes but is not limited to a multiverse optimization algorithm, a zebra optimization algorithm, and a genetic algorithm.
5. The design method of the all-perovskite tandem solar cell according to claim 4, characterized in that: By adjusting the thickness of the transparent electrode layer (2), the peak position of the coherent reflection peak generated by the all-perovskite tandem solar cell in the 300-700 nm band can be adjusted.
6. The design method of the all-perovskite tandem solar cell according to claim 5, characterized in that: By adjusting the thickness of the interconnect layer (H), the coherent reflection phenomenon of the all-perovskite stacked solar cell in the 700-1000nm band is weakened.
7. The design method of the all-perovskite tandem solar cell according to claim 6, characterized in that: When the optimized thickness of the interconnection layer (H) exceeds the experimentally producible range, the thickness of the interconnection layer (H) is reduced and the thickness is compensated by other alternative materials.
8. The design method of the all-perovskite tandem solar cell according to claim 7, characterized in that: When the material of the interconnect layer (H) is SnO2, the alternative material is indium tin oxide.
9. A design system for all-perovskite tandem solar cells, characterized in that: Applicable to the design method of the all-perovskite tandem solar cell as described in any one of claims 1 to 8.
10. An all-perovskite tandem solar cell, characterized in that: The solar cell is manufactured by the design method of the all-perovskite tandem solar cell as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Three-junction solar cell and preparation method thereof
CN118234270A
Method for acquiring optimal photoelectric efficiency of perovskite solar cell
CN118888466A
Perovskite thin film solar cell performance optimization method and system
CN118917221A
Perovskite thin film solar cell
CN119012728A
Full-perovskite laminated solar cell and preparation method thereof
CN119277883A
Cited By
Novel dye-sensitized solar cell optimization method
CN121598650A
Organic solar cell parameter optimization method based on light field numerical simulation
CN122242308A
A Method for Optimizing Organic Solar Cell Parameters Based on Numerical Simulation of Light Field
CN122242308B